Corporate Governance and Financial Performance of Firms Listed on the Uganda Securities Exchange - Brandon Turyahikayo (Uganda Christian University, 2023)
This research delves into the relationship between corporate governance and the financial performance of firms listed on the Uganda Securities Exchange. The study recognizes the growing significance of corporate governance in contemporary organizations and its impact on overall financial outcomes. With a focus on the public sector, the research aims to comprehend the multifaceted dimensions of financial performance assessment and its correlation with corporate governance mechanisms. The research is prompted by the observation that corporate governance issues have been primarily investigated in specific sectors, such as banking, leaving other industries, notably brewing, with insufficient attention. Despite a legislative framework in East Africa, corporate governance challenges persist, leading to scandals and unethical behavior among directors, thereby posing threats to stakeholders' interests. Moreover, recent failures of companies like insurance and banking institutions have exposed weaknesses in corporate governance practices. The overarching objective of the study is to explore the interplay between corporate governance practices and the financial performance of firms on the Uganda Securities Exchange. The study aims to answer specific research questions, such as the relationships between board size, board composition, accountability, and financial performance. By analyzing data from a variety of firms listed on the Uganda Securities Exchange, the research seeks to draw insights into how corporate governance practices impact the financial health and success of these entities. Through an in-depth analysis of the relationships between corporate governance and financial performance, this study aims to provide actionable insights that could aid firms in adopting better governance practices. Ultimately, the research contributes to the broader understanding of corporate governance's role in achieving sustainable financial success and can potentially guide decision-makers in formulating policies that foster responsible and effective corporate governance practices across various sectors.
This is a dissertation.